Adolescent Bullying and Family Therapy - Kate Fogarty (EDIS)
“As much as parents like to think that bullying is something that’s outgrown in childhood, unfortunately it’s actually on the increase in adolescence. There are various individual and school-based approaches to dealing with bullying, but a new intervention that you might find surprising is none other than family therapy.” This 2-page Family Album Radio transcript was written by Kate Fogarty and published by the UF Department of Family, Youth and Community Sciences, August 2012.